2022
DOI: 10.3389/fcell.2022.861451
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Biomarkers for Ionizing Radiation Injury

Abstract: Accidental radiation exposures such as industrial accidents and nuclear catastrophes pose a threat to human health, and the potential or substantial injury caused by ionizing radiation (IR) from medical treatment that cannot be ignored. Although the mechanisms of IR-induced damage to various organs have been gradually investigated, medical treatment of irradiated individuals is still based on clinical symptoms. Hence, minimally invasive biomarkers that can predict radiation damage are urgently needed for appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 102 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…We also noticed that miR-150 tended to be highly expressed in the RT response samples, implying it may play a role in radiosensitivity. Previous report showed that the expression of miR-150 decreased significantly in serum after irradiation in animal studies (Jia and Wang, 2022). Recently, miR-150-5p were confirmed to target ZEB1 and caused mRNA degradation, thus blocking EMT (Lu et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…We also noticed that miR-150 tended to be highly expressed in the RT response samples, implying it may play a role in radiosensitivity. Previous report showed that the expression of miR-150 decreased significantly in serum after irradiation in animal studies (Jia and Wang, 2022). Recently, miR-150-5p were confirmed to target ZEB1 and caused mRNA degradation, thus blocking EMT (Lu et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…Increased attention to miRNAs in radiation biology is associated with the search for molecular diagnostic biomarkers to assess the level of IR-induced damage to organisms, including radiation-related premature cellular senescence ( Table 3 ) [ 211 ].…”
Section: Radiation-induced Cellular Senescencementioning
confidence: 99%
“…MicroRNAs (miRNAs) are highly conserved, non-coding RNA fragments composed of 19–25 nucleotides that negatively regulate ~ 30% of human gene expression by binding to messenger RNA [ 72 , 73 ]. A number of miRNAs have been linked to non-cancer treatment-induced cardiac dysfunction, including cardiac hypertrophy (e.g., miR-1, miR-133a), fibrosis (e.g., miR-21), coronary artery disease (e.g., miR-624, miR-340), and chronic heart failure (miR-221, miR-21, miR-409-5p, miR-376a, miR-154) [ 74 ].…”
Section: Advances In Biomarkersmentioning
confidence: 99%